DEVELOPMENT OF A MODEL FOR APPLYING CORRELATION CRYPTANALYSIS TO COMBINATORIAL GENERATORS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the application of the method of correlation cryptanalysis for stream encryption algorithms based on shift registers with feedback. To evaluate the cryptographic stability of the stream encryption algorithm by the method of correlation cryptanalysis, the correlation cryptanalysis method was applied to the Geffe combinatorial algorithm, stream encryption algorithm A5, and a mathematical model was developed to apply the correlation cryptanalysis method to combinatorial generators. This model serves as the basis for evaluating the stream encryption algorithm by the method of correlation cryptanalysis.